Legal Pluralism in Corporate Social Responsibility (CSR) Based on Tri Hita Karana in Bali - I Wayan Suarjana (NOTARIIL Jurnal Kenotariatan, 2025)
Corporate social responsibility based on Tri Hita Karana in Bali creates a unique coexistence between positive law and customary law in corporate governance. This study analyzes the legal coexistence in Tri Hita Karana CSR, examines normative conflict resolution mechanisms, and evaluates the consistency of legal pluralism. The normative juridical method uses legal materials analysis through regulatory, conceptual, and comparative approaches. The results indicate that coexistence manifests in three constructions: complementary harmonization, selective adaptation, and continuous negotiation. Conflict resolution is regulated through a hybrid legal structure with strong legitimacy in the hierarchy of norms. Legal pluralism creates systemic consistency that integrates local values with national standards.